A novel mitochondrial genome fragmentation pattern in Liposcelis brunnea, the type species of the genus Liposcelis (Psocodea: Liposcelididae) - Feng, Shiqian; Li, Hu; Song, Fan; Wang, Yannan; Stejskal, Václav; Cai, Wanzhi; Li, Zhihong (International journal of biological macromolecules, 2019)
Booklice in the genus Liposcelis (Psocodea: Liposcelididae) are essential storage pests worldwide. Fragmented mt genomes have been identified in the Liposcelis species together with the typical mitochondrial (mt) genome, which is a single circular chromosome with 37 genes. Gene rearrangement, pseudogenes, and repeat regions (RRs) are very common among fragmented mt genomes. We sequenced the mt genome of the booklouse L. brunnea, the type species of the genus Liposcelis. We identified 37 genes in the mt genome of L. brunnea, which was fragmented into three chromosomes. The chromosomes I, II, III were 7.3 kb, 5.5 kb, and 5.3 kb in size with 9, 19, and 15 genes, respectively. In addition, 16 pseudogenes and four repeat regions were present in three chromosomes. Gene rearrangement in the mt genome of L. brunnea was obvious compared to that in other mt genomes in the genus Liposcelis. We found a possible correlation among mt genome rearrangement, the morphological classification standard, and phylogenetic relationships. In summary, a three-chromosome mt genome in an insect was identified for the first time, which may aid in understanding mt genome fragmentation, gene rearrangement, and evolution.
Keywords: Evolution, Molecular; Insecta; molekulární evoluce; Genes, Insect; Gene Order; Genome, Mitochondrial; fylogeneze; Animals; hmyz; Phylogeny; genom mitochondriální; zvířata; pořadí genů; multigenová rodina; Multigene Family; hmyzí geny